2013
DOI: 10.1021/jf400823s
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Quantification of the Health-Relevant Anthocyanin and Phenolic Acid Profiles in Commercial Cultivars and Breeding Selections of Blueberries (Vaccinium spp.)

Abstract: Anthocyanins and phenolic acids are major secondary metabolites in blueberry with important implications for human health maintenance. An improved protocol was developed for the accurate, efficient, and rapid comparative screening for large blueberry sample sets. Triplicates of six commercial cultivars and four breeding selections were analyzed using the new method. The compound recoveries ranged from 94.2 to 97.5 ± 5.3% when samples were spiked with commercial standards prior to extraction. Eighteen anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 45 publications
9
75
3
2
Order By: Relevance
“…Blackcurrant and maqui berry contained delphinidins as primary (58% and 78%) and cyanidins as secondary (42% and 21%) anthocyanins, and most pigments were present in the diglycosylated, non-acylated form as reported earlier [28,29]. Blueberry and Concord grape had the most complex anthocyanin profiles enriched with malvidins (34% and 7%), petunidins (23% and 19%), and delphinidins (29% and 37%), which were predominantly monoglycosylated and non-acylated (blueberry) or acylated (Concord grape), as observed previously [30,31]. Blueberry (100%) and blackberry (93%) were the best sources of monoglycosylated anthocyanins, while blackcurrant (84%) and maqui berry (62%) were predominantly diglycosylated.…”
Section: Resultssupporting
confidence: 60%
“…Blackcurrant and maqui berry contained delphinidins as primary (58% and 78%) and cyanidins as secondary (42% and 21%) anthocyanins, and most pigments were present in the diglycosylated, non-acylated form as reported earlier [28,29]. Blueberry and Concord grape had the most complex anthocyanin profiles enriched with malvidins (34% and 7%), petunidins (23% and 19%), and delphinidins (29% and 37%), which were predominantly monoglycosylated and non-acylated (blueberry) or acylated (Concord grape), as observed previously [30,31]. Blueberry (100%) and blackberry (93%) were the best sources of monoglycosylated anthocyanins, while blackcurrant (84%) and maqui berry (62%) were predominantly diglycosylated.…”
Section: Resultssupporting
confidence: 60%
“…In the reported 18 species, the content of delphenidin 3-O-(6''-acetyl) glucoside, cyanidin 3-O-(6''-acetyl) glucoside, malvidin 3-O-(6''-acetyl), petunidin 3-O-(6''-acetyl) glucoside, and malvidin 3-O-(6''-acetyl) glucoside, which do not exist in our study, is only 4.6%. Compared with previous study (Yousef et al, 2013), our study found only 11 species which constitute the majority of the anthocyanins. Thus the abundance of other species is in accordance with most studies (Cheng et al, 2014).…”
Section: Discussioncontrasting
confidence: 91%
“…In terms of the compounds of the GBBAEs, Yousef et al (2013) showed the richest species of 18 anthocyanins in blueberry. In the reported 18 species, the content of delphenidin 3-O-(6''-acetyl) glucoside, cyanidin 3-O-(6''-acetyl) glucoside, malvidin 3-O-(6''-acetyl), petunidin 3-O-(6''-acetyl) glucoside, and malvidin 3-O-(6''-acetyl) glucoside, which do not exist in our study, is only 4.6%.…”
Section: Discussionmentioning
confidence: 99%
“…However it is important to note that fresh, not freeze-dried plums were used for extraction in that study. Several possible reasons for the relatively low % (~20%) of bound phenolics, in QG and BD, include the high content of anthocyanins relative to the European plum cultivars, which are often nearly completely extractable in acidified methanol following homogenization (Yousef et al, 2013), and the fact that QG/BD samples were freeze dried prior to extraction. The use of freeze-drying has been shown to significantly enhance the extractability of several phenolic acids in blueberries (Yousef et al, 2013).…”
Section: Bound Phenolicsmentioning
confidence: 99%